Local journalists’ response to foreign tourist misconduct in post-pandemic Bali - Nurhajati, Lestari; Wijayanto, Xenia Angelica; Rembulan, Yosephine Avi Ayu (Program Studi Ilmu Komunikasi, 2025)
The emergence of Bali as a world tourist destination has been accompanied by a series of problems involving misconduct by foreign tourists. This paper examines how local journalists cope with these issues whilst managing professional ethics, political, and economic pressures. The qualitative approach enabled data collection through Focus Group Discussions (FGDs) with four print journalists and one television journalist. The results indicate that tourist violations are not novel but have become apparent due to the amplification of social media and the following news reporting. The primary roles of journalists include acting as watchdogs, exposing ineffective law enforcement, educating people about norms and visa policies, and addressing community concerns. However, these functions are limited by output requirements, financial reliance, and sensitivities surrounding the safeguarding of Bali's tourism image. Such tension illustrates that ethical journalism can be difficult in a society that relies on tourism.